STRATEGI PENINGKATAN KOMPETENSI GURU DI ERA DIGITAL - Cindi Amelia; Lailan Fadila (Cendekia Madani Nusantara, 2024)
The current rapid development of digital technology has changed the educational landscape significantly. In this era of globalization, the role of teachers is becoming increasingly strategic in preparing future generations. Teacher quality is the key to ensuring the effectiveness and relevance of education amidst the dynamics of an ever-developing era. In line with this, education managers must provide a positive response by continuing to improve the quality of the education programs offered. This research aims to uncover teacher competency needs in the digital era, with a focus on the strategies needed to improve the quality of teacher education. The research method used is literature analysis and case studies. Data was collected from various relevant literature sources, as well as through case studies involving teachers who actively use digital technology in the learning process. The research results show that in the current digital era, teachers need to develop various competencies, such as the ability to use technology, interpersonal communication, and innovative learning strategies. Improving the quality of teacher education needs to be encouraged through the development of training programs that strengthen these competencies. The conclusion of this research is that to face the demands of the digital era, teachers need to have strong competencies, and the development of these competencies needs to be supported through appropriate strategies in teacher education programs.